A 0.45 W 18% PAE E-Band Power Amplifier in 100 nm InGaAs pHEMT Technology. (29th March 2018) - Zhao, Dixian; Yi, Yongran
Abstract : This paper describes a fully integrated power amplifier (PA) in 100 nm InGaAs pHEMT process for E-band point-to-point communications. The device size and biasing conditions are optimized to enhance the overall performance at millimeter-wave frequencies. The complete PA consists of two unit PAs and each unit PA has four stages to improve the gain while ensuring stability from dc to the operating frequencies. A 4-way zero-degree combiner (in the unit PA) and a 2-way λ /2 combiner are used to boost the output power. Occupying 5 mm 2, the proposed PA achieves an output power of 0.45 W with 17.9% PAE at 74 GHz.